1990
DOI: 10.1177/019459989010200614
|View full text |Cite
|
Sign up to set email alerts
|

The Sphenoid Sinus—A Site for Metastasis

Abstract: While metastatic tumors to the nose and the paranasal sinuses overall are unusual, metastasis to the sphenoid sinus is exceedingly rare. Presented are 26 cases of metastasis to the sphenoid sinus. Seven were treated at UCLA between 1955 and 1988, and 19 additional cases were discovered from a search of the medical literature. The patients ranged from 14 months to 79 years of age. The most common tumor sites from which sphenoid metastases arose were the prostate and the lung. In 11 of the 26 cases, the sphenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
0
39
0
1
Order By: Relevance
“…Metastatic disease has been reported to involve the sphenoid sinus, with prostate, renal, and lung cancers predominating. 13,14 The use of MR imaging is helpful in the preoperative evaluation of these lesions, both in terms of providing information about the possible abnormality and to determine the relationship to surrounding vital structures. Furthermore, MR imaging is superior to CT in differentiating tumor from obstructed secretions.…”
Section: Commentmentioning
confidence: 99%
“…Metastatic disease has been reported to involve the sphenoid sinus, with prostate, renal, and lung cancers predominating. 13,14 The use of MR imaging is helpful in the preoperative evaluation of these lesions, both in terms of providing information about the possible abnormality and to determine the relationship to surrounding vital structures. Furthermore, MR imaging is superior to CT in differentiating tumor from obstructed secretions.…”
Section: Commentmentioning
confidence: 99%
“…It was reported that 7% of metastatic paranasal sinus tumors involved the sphenoid sinus [6]. Mickel and Zimmerman [7] reviewed 26 cases with metastatic tumors of sphenoid sinuses ranged from 14 months to 79 years of age. The most common primary tumor sites were prostate and lung and only one of them was neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other primary sources for secondaries in the PNS that should be borne in mind include prostate, lung and thyroid adenocarcinomas [2]. RCC is known to be one of the commonest [5] potential primary tumors displaying metastases in this location [1,[4][5][6]. The present case serves to alert the treating surgeon to the occurrence of such symptoms secondary to the spread of asymptomatic primary lesions elsewhere in the body.…”
Section: Commentmentioning
confidence: 93%
“…The PNS tend to be implicated whenever visual abnormalities are detected, and when present these related ocular signs are frequently the sentinel symptoms [3]. Thus, patients with such symptoms ought to be vigorously evaluated for the possibility of PNS [4] tumors.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation